Efficient pH-sensitive nanosystem containing Atractylenolide Ⅰ for improving tumor hypoxic microenvironment and photothermal conversion capability for synergistic treatment of colorectal cancer - Zhu, Yuqing; Ye, Qiang; Feng, Shi; Fu, Xiujuan; Chen, Siwei; Liu, Hao; Ning, Jialin; Li, Yaling; Zhang, Dan (Frontiers in Nanotechnology, 2025)
BackgroundPhotodynamic therapy (PDT) displays several beneficial characteristics, but it is still limited by the poor water solubility of photosensitizers, the insufficient targetability of the system, and the hypoxic microenvironment of tumors. It has been demonstrated that Atractylenolide Ⅰ(ATL-1) not only alleviates the tumor hypoxic microenvironment but also has considerable potential in antitumor therapy. Hence the combination of the above two is anticipated to achieve more efficacious antitumor effects.MethodsNanosystems of pH-sensitive materials coated with Atractylenolide I and Ce6 were prepared by thin-film hydration method for targeted delivery to the acidic microenvironment of colorectal cancer. The morphology and stability of the nanosystems were evaluated by particle size, zeta potential, and phenology. The in vitro anti-tumor activity and mechanism of the nanosystems were evaluated using CCK-8 assay, live/dead cell double staining assay, ROS level, WB, and flow-through. Establishment of mouse ectopic colorectal cancer model. The safety, in vivo anti-tumor activity, and mechanism of the nanosystems were evaluated by mouse tumor volume change curves, biochemical indexes, and H&E staining.ResultsThe results demonstrated that the prepared ATL-1/Ce6-pH Lip had desirable physicochemical properties, drug release behaviors, cellular uptake and cytotoxicity, satisfactory biocompatibility and in vivo antitumor effect.ConclusionThis paper described the process of co-loading ATL-1 and Ce6 into pH-sensitive liposomes (ATL-1/Ce6-pH Lip), which utilized the tumor-specific acidic microenvironment to facilitate the release of drugs for the synergistic treatment of CRC. Our findings demonstrated that ATL-1 enhanced the oxygen content of the microenvironment, providing the essential raw material for the generation of ROS. At the same time, PDT was observed to obstruct blood vessels in tumor tissues, thereby damaging the blood supply to the tumor tissues. Additionally, PDT was demonstrated to destroy blood vessels in tumor tissues, leading to more exposure of the tumor cells to the drug environment. When it comes to the ATL-1/Ce6-pH Lip, which successfully combine the above two therapeutic approaches, chemotherapy and PDT treatment,a synergistic effect can be expected. In conclusion, the ATL-1/Ce6-pH Lip has considerable potential in the treatment of CRC.